Strategi pengembangan usaha tenun ikat Bima melalui penerapan Model Triple Helix: (STUDI KASUS PADA KAMPUNG TENUN NTOBO KOTA BIMA) - Chairul Hudaya; Diah Anggeraini Hasri; Fani Fitriani (Owner : Riset dan Jurnal Akuntansi, 2023)
One of the ways to develop Bima Ikat is by involving the roles of universities, the government and business people known as the triple helix model. This study aims to analyze the role of government, academics and business people in the development of woven textiles in the city of Bima. This research use desciptive qualitative approach. The population in this study were all weavers in the weaving village of Ntobo sub-district, Bima City and the sample used Quota sampling with a specified number of 300 respondents. The results of the study show that there are three priority alternative strategies that can be proposed as follows; Assistance activities by the tourism agency have not been supported by cross-stakeholder coordination in Bima City, weavers as a source of livelihood are constrained by relatively expensive product prices and weaving activities have not yet scaled the production of creative industries that need to be supported by government regulations. According to the data analysis and research results, it can be concluded that the role of each element related to the development of Ikat in Bima City is carried out through three main strategies. Based on the results of the research findings, the suggestion is that it is expected that woven woven craftsmen whose business has developed consistently, need to maintain even more development with strategies and preventive efforts against various possibilities.